Plastic powder coating with flame retardant and self-cleaning properties and preparation method thereof

By introducing components such as mesoporous silicon dioxide wafers and polyphenylene sulfides into plastic powder coatings, combining PVDF and BMIMPF6 ionic liquids, the problem of insufficient flame retardant performance and self-cleaning performance in the prior art is solved, and low cost is achieved , efficient flame retardant and self-cleaning effect.

CN118755315BActive Publication Date: 2025-01-03SUZHOU LONGCAI MOLDING POWDER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410918624.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-10
Publication Date
2025-01-03
Estimated Expiration
2044-07-10

AI Technical Summary

Technical Problem

Existing plastic powder coatings have problems with flame retardant properties and self-cleaning properties, which can pose potential risks to the environment and health, and are costly and have poor durability.

Method used

By introducing mesoporous silicon dioxide wafers, polyphenylene sulfide and PVDF into the components, the flame retardant properties are achieved by using the physical isolation of mesoporous silicon dioxide wafers and the chemical properties of polyphenylene sulfide and PVDF, and by polyphenylene sulfide and PVDF, it is also possible to achieve flame retardant properties through polyphenylene sulfide and PVDF. The synergistic effect of sulfide, PVDF, BMIMPF6 ionic liquid and polymethylphenylsiloxane achieves low-cost and surface self-cleaning properties.

Benefits of technology

It realizes low-cost plastic powder coatings without using halogen flame retardants, with excellent flame retardant properties and long-lasting self-cleaning properties, avoiding environmental and health risks, and at low cost.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a plastic powder coating with flame retardant and self-cleaning properties and a preparation method thereof. The plastic powder coating comprises a base resin, a crosslinking agent, a self-cleaning agent, a flame retardant, a degassing agent, a smoke suppressant, a leveling agent, and a filler. The self-cleaning agent comprises polyphenylene sulfide, PVDF, BMIMPF6 ionic liquid, and polymethylphenylsiloxane. The flame retardant comprises a mesoporous silica sheet, polyphenylene sulfide, and PVDF. The preparation method comprises the steps of preparing a mesoporous silica sheet, preparing nano calcium carbonate, premixing, melt extrusion, grinding and screening, and the like. By introducing mesoporous silica sheets, polyphenylene sulfide, and PVDF into the components, the flame retardant property is achieved by utilizing the physical isolation effect of the mesoporous silica sheets and the chemical properties of polyphenylene sulfide and PVDF; by adding the synergistic effect of the four components of polyphenylene sulfide, PVDF, BMIMPF6 ionic liquid, and polymethylphenylsiloxane, low cost and surface self-cleaning property are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of surface protection materials, and in particular to a plastic powder coating with flame retardant and self-cleaning properties and a preparation method thereof. Background Art

[0002] Plastic powder coating is a kind of coating material widely used on various surfaces. It is environmentally friendly, durable and beautiful, and is highly favored in the market. It is mainly composed of resin, pigment, filler and additives. It is evenly attached to the surface of the coated object by spraying to form a solid protective film. It has excellent adhesion, wear resistance and weather resistance, can resist chemical corrosion and ultraviolet radiation, and maintain bright colors and gloss for a long time; it also has good environmental performance, is non-toxic and odorless, does not produce volatile organic compounds (VOC), is environmentally friendly, and is suitable for a variety of material surfaces, such as metal, wood, plastic, etc., and is widely used in construction, home, automobile and other fields.

[0003] The flame retardant properties of existing plastic powder coatings are mostly achieved by adding conventional flame retardants, such as halogen flame retardants. These flame retardants contain halogen elements such as chlorine (Cl), bromine (Br), iodine (I) and fluorine (F). Although they have a highly effective flame retardant effect, they may also produce harmful gases and byproducts, posing potential risks to the environment and health. The self-cleaning properties of plastic powder coatings are achieved by introducing certain components to make their surfaces super-hydrophobic, or by introducing photocatalysts to degrade organic pollutants under the action of ultraviolet rays, thereby achieving the purpose of self-cleaning. However, there are problems such as high cost and poor durability.

[0004] Therefore, it is necessary to develop a plastic powder coating and a preparation method thereof which does not use halogen flame retardants, is low-cost and has a long-lasting surface self-cleaning property. Summary of the invention

[0005] In view of this, the present invention provides a plastic powder coating with flame retardant and self-cleaning properties and a preparation method thereof, by introducing mesoporous silica sheets, polyphenylene sulfide and PVDF into the components, utilizing the physical isolation effect of the mesoporous silica sheets and the chemical properties of polyphenylene sulfide and PVDF to achieve flame retardant properties; by adding the synergistic effect of the four components of polyphenylene sulfide, PVDF, BMIMPF6 ionic liquid and polymethylphenylsiloxane, low cost and surface self-cleaning properties are achieved.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a plastic powder coating having flame retardant and self-cleaning properties, the plastic powder coating comprising a base resin, a cross-linking agent, a self-cleaning agent, a flame retardant, a degassing agent, a smoke suppressant, a leveling agent, and a filler;

[0008] The base resin includes 26-33 parts by weight of polyethylene resin and 53-61 parts by weight of polypropylene resin;

[0009] The cross-linking agent comprises 1.2-2.5 parts by weight of benzoyl peroxide and 0.3-0.8 parts by weight of tert-butyl perbenzoate;

[0010] The self-cleaning agent comprises 0.6-1.3 parts by weight of polyphenylene sulfide, 1.4-2.6 parts by weight of PVDF, 0.1-0.2 parts by weight of BMIMPF6 ionic liquid, and 0.8-1.1 parts by weight of polymethylphenylsiloxane;

[0011] The flame retardant comprises 12.1-13.2 parts by weight of mesoporous silica sheets;

[0012] The degassing agent includes 0.5-0.8 parts by weight of SA500 degassing agent and 0.4-0.9 parts by weight of T961 degassing agent;

[0013] The smoke suppressant comprises 0.1-0.3 parts by weight of molybdenum oxide, 0.2-0.6 parts by weight of zinc borate, and 0.06-0.2 parts by weight of ferrocene;

[0014] The leveling agent includes 1.3-1.7 parts by weight of 503 leveling agent;

[0015] The filler comprises 5-11 parts by weight of nano calcium carbonate;

[0016] The particle size of the plastic powder coating is 50-100 microns.

[0017] Preferably, the mesoporous silica sheet has an average pore size of 5-15 nanometers, a pore volume of 0.7-0.9 cubic centimeters per gram, a specific surface area of ​​500-600 square meters per gram, a thickness of 0.5-1.1 micrometers, and an average sheet surface diameter of 6-13 micrometers.

[0018] Preferably, the primary crystal particle size of the nano calcium carbonate is 20-70 nanometers, and the secondary crystal particle size is 1-2 micrometers.

[0019] Preferably, the polyethylene resin is high-density polyethylene with a weight average molecular weight of 90,000-200,000.

[0020] Preferably, the polypropylene resin is random copolymer polypropylene with a weight average molecular weight of 25,000-60,000 and an ethylene monomer content of 2.3%-4.2%.

[0021] In a second aspect, the present invention provides a method for preparing the plastic powder coating having flame retardant and self-cleaning properties as described above, the method for preparing the plastic powder coating having flame retardant and self-cleaning properties comprising the following steps:

[0022] Preparation of mesoporous silica sheets: 3-6 parts by weight of amine salt type cationic surfactant, 20-50 parts by weight of orthosilicate, 30-90 parts by weight of deionized water, and 0.5-4 parts by weight of 36% hydrochloric acid are uniformly mixed to obtain a precursor sol, the precursor sol is dripped onto a super-hydrophilic glass substrate to form a discontinuous liquid film, vacuum dried at 20-37° C. to reduce the water content to less than 0.5%, to obtain a sheet layer, the sheet layer is blown off with nitrogen, the sheet layer is heat-treated at 500-900° C., and then appropriately crushed and sieved to obtain the mesoporous silica sheet;

[0023] Preparation of nano calcium carbonate: preparing an organic acid calcium suspension, wherein the mass concentration of the organic acid calcium is 21%-38%, adding a saturated ammonium carbonate solution, wherein the amount of ammonium carbonate added is 1.05-1.3 times the molar amount of calcium in the organic acid calcium, adding the solution uniformly, and the adding time is 20-50 minutes. The reaction temperature is 20-40° C., the stirring speed of the reaction system is 200-400 rpm, and the reaction pressure is normal pressure. After the addition of the saturated ammonium carbonate solution is completed, stirring and reacting for 40-70 minutes, filtering out the solid, washing with deionized water to neutrality, drying to a water content of less than 0.1%, and then modifying the solution with a silane coupling agent to obtain the nano calcium carbonate;

[0024] Weigh the raw materials: weigh 26-33 parts by weight of polyethylene resin, 53-61 parts by weight of polypropylene resin, 1.2-2.5 parts by weight of benzoyl peroxide, 0.3-0.8 parts by weight of tert-butyl perbenzoate, 0.6-1.3 parts by weight of polyphenylene sulfide, 1.4-2.6 parts by weight of PVDF, 0.1-0.2 parts by weight of BMIMPF6 ionic liquid, 0.8-1.1 parts by weight of polymethylphenylsiloxane, 12.1-13.2 parts by weight of the mesoporous silica sheet, 0.5-0.8 parts by weight of SA500 degassing agent, 0.4-0.9 parts by weight of T961 degassing agent, 0.1-0.3 parts by weight of molybdenum oxide, 0.2-0.6 parts by weight of zinc borate, 0.06-0.2 parts by weight of ferrocene, 1.3-1.7 parts by weight of 503 leveling agent, and 5-11 parts by weight of nano calcium carbonate;

[0025] Premixing: Put the weighed raw materials into a premixing device, and premix them for 3-9 hours in an inert gas atmosphere at 280-310° C. and a stirring speed of 50-200 rpm to obtain a premix;

[0026] Melt extrusion: the premix is ​​placed in a melt extrusion device and extruded at 260-290°C and 0.3-1.4MPa to obtain plastic powder raw material particles with a particle size of 1-5 mm;

[0027] Grinding and screening: the plastic powder raw material particles are placed in a grinding device, and dry ice is added. The mass ratio of the plastic powder raw material particles to the dry ice is maintained at 7-20:1. The dry ice needs to be replenished intermittently in batches to keep the mass ratio of the plastic powder raw material particles to the dry ice within the range. During the grinding process, particles with a particle size of less than 100 microns are screened out, and then screened using a 50-micron aperture sieve. Particles with a particle size less than 50 microns are returned to the melt extrusion step to obtain a 50-100 micron plastic powder coating.

[0028] Preferably, the amine salt type cationic surfactant includes octadecylamine (stearylamine) hydrochloride, triethanolamine monostearate formate, N,N-dimethyloctadecylamine hydrochloride, and the orthosilicate includes ethyl orthosilicate and tetramethyl silicate.

[0029] Preferably, the method for preparing the super hydrophilic glass substrate comprises the following steps:

[0030] Dissolving 9-13 parts by weight of tetrabutyl titanate in 40-70 parts by weight of anhydrous ethanol, and then adding 0.03-0.08 parts by weight of glacial acetic acid to obtain a precursor solution;

[0031] Add 30-80 parts by weight of deionized water to the precursor solution for hydrolysis, react at 20-40° C. for 2-5 hours to obtain a titanium dioxide nanoparticle gel;

[0032] The titanium dioxide nanoparticle gel is sprayed onto a clean glass substrate, and dried at 25-38° C. under normal pressure to remove the solvent, thereby obtaining a glass plate pre-coated with titanium dioxide nanoparticles;

[0033] The glass plate pre-coated with titanium dioxide nanoparticles is heat-treated at 350-400° C. for 3-8 hours to obtain the super-hydrophilic glass substrate.

[0034] Preferably, the organic acid calcium includes calcium citrate, calcium succinate, and calcium lactate.

[0035] Preferably, the silane coupling agent includes vinyltrimethoxysilane and vinyltriethoxysilane.

[0036] Compared with the prior art, the present invention has the following beneficial technical effects: ① By introducing a low-density mesoporous silica flake layer into the components, the mesoporous silica flake layer can form a physical isolation layer on the surface of the plastic powder coating after it encounters fire, thereby preventing oxygen from contacting the plastic powder coating, thereby avoiding intensified combustion; ② The flame retardants polyphenylene sulfide and PVDF are then introduced, and the physical isolation effect of the mesoporous silica flakes and the chemical properties of polyphenylene sulfide and PVDF are used to achieve flame retardant properties, thereby further enhancing the flame retardant properties of the plastic powder coating of this application; ③ By introducing polyphenylene sulfide, PVDF, BMIMPF6 ionic liquid and polymethylphenylsiloxane into the components, the surface of the plastic powder coating after molding has hydrophobic properties, thereby giving it self-cleaning properties. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is described in detail below in conjunction with embodiments.

[0038] It should be noted that the following embodiments and features in the embodiments may be combined with each other in the absence of conflict; and, based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in the field without making any creative work are within the scope of protection of the present disclosure.

[0039] It should be noted that various aspects of the embodiments within the scope of the appended claims are described below. It should be apparent that the aspects described herein can be embodied in a wide variety of forms, and any specific structure and / or function described herein is merely illustrative. Based on this disclosure, it should be understood by those skilled in the art that an aspect described herein can be implemented independently of any other aspect, and two or more of these aspects can be combined in various ways. For example, any number of aspects described herein can be used to implement the device and / or practice the method.

[0040] The plastic powder coating with flame retardant and self-cleaning properties and the preparation method thereof provided by the present invention achieve flame retardant properties by introducing mesoporous silica sheets, polyphenylene sulfide and PVDF into the components, utilizing the physical isolation effect of the mesoporous silica sheets and the chemical properties of polyphenylene sulfide and PVDF; and achieve low cost and surface self-cleaning properties by adding the synergistic effect of the four components of polyphenylene sulfide, PVDF, BMIMPF6 ionic liquid and polymethylphenylsiloxane.

[0041] The present invention provides a plastic powder coating with flame retardant and self-cleaning properties, the plastic powder coating comprising a base resin, a cross-linking agent, a self-cleaning agent, a flame retardant, a degassing agent, a smoke suppressant, a leveling agent, and a filler;

[0042] The base resin includes 26-33 parts by weight of polyethylene resin and 53-61 parts by weight of polypropylene resin;

[0043] The cross-linking agent includes 1.2-2.5 parts by weight of benzoyl peroxide and 0.3-0.8 parts by weight of tert-butyl perbenzoate;

[0044] The self-cleaning agent comprises 0.6-1.3 parts by weight of polyphenylene sulfide, 1.4-2.6 parts by weight of PVDF, 0.1-0.2 parts by weight of BMIMPF6 ionic liquid, and 0.8-1.1 parts by weight of polymethylphenylsiloxane;

[0045] The flame retardant comprises 12.1-13.2 parts by weight of mesoporous silica sheets;

[0046] The degassing agent includes 0.5-0.8 parts by weight of SA500 degassing agent and 0.4-0.9 parts by weight of T961 degassing agent;

[0047] The smoke suppressant comprises 0.1-0.3 parts by weight of molybdenum oxide, 0.2-0.6 parts by weight of zinc borate, and 0.06-0.2 parts by weight of ferrocene;

[0048] The leveling agent includes 1.3-1.7 parts by weight of 503 leveling agent;

[0049] The filler includes 5-11 parts by weight of nano calcium carbonate;

[0050] The particle size of plastic powder coating is 50-100 microns.

[0051] More preferably, the weight average molecular weight of polyphenylene sulfide is 5000-7000, and the flame retardancy reaches UL94V-0.

[0052] More preferably, PVDF refers to polyvinylidene fluoride, and its weight average molecular weight is 400,000-450,000.

[0053] It should be noted that BMIMPF6 ionic liquid refers to 1-butyl-3-methylimidazolium hexafluorophosphate, which has the effect of interface modification.

[0054] It should be noted that polyphenylene sulfide has a high melting point, reaching above 260°C, and will crystallize and solidify before other components. During the preparation of the plastic powder coating layer, the surface temperature drops quickly, and the polyphenylene sulfide component solidifies into a solid first, which causes the polyphenylene sulfide component to be enriched on the surface and form a hydrophobic surface. PVDF, BMIMPF6 ionic liquid and polymethylphenylsiloxane can enhance the surface hydrophobicity and improve the self-cleaning performance of the plastic powder coating.

[0055] It should be noted that molybdenum oxide, zinc borate, ferrocene, and 503 leveling agent are all commercially available products.

[0056] Preferably, the mesoporous silica sheet has an average pore size of 5-15 nanometers, a pore volume of 0.7-0.9 cubic centimeters per gram, a specific surface area of ​​500-600 square meters per gram, a thickness of 0.5-1.1 micrometers, and an average sheet surface diameter of 6-13 micrometers.

[0057] More preferably, the density of the mesoporous silica sheet is 0.25-0.66 g / cm3.

[0058] It should be noted that polyphenylene sulfide and PVDF also have flame retardant effects.

[0059] Preferably, the primary crystal particle size of the nano calcium carbonate is 20-70 nanometers, and the secondary crystal particle size is 1-2 micrometers.

[0060] It should be noted that nano calcium carbonate, as a filler in the plastic powder coating of the present application, can make it have excellent properties such as wear resistance and surface finish.

[0061] Preferably, the polyethylene resin is high-density polyethylene with a weight average molecular weight of 90,000-200,000.

[0062] Preferably, the polypropylene resin is a random copolymer polypropylene with a weight average molecular weight of 25,000-60,000 and an ethylene monomer content of 2.3%-4.2%.

[0063] The present invention also provides a method for preparing the above-mentioned plastic powder coating with flame retardant and self-cleaning properties, and the method for preparing the plastic powder coating with flame retardant and self-cleaning properties comprises the following steps:

[0064] Preparation of mesoporous silica sheets: 3-6 parts by weight of an amine salt type cationic surfactant, 20-50 parts by weight of an orthosilicate, 30-90 parts by weight of deionized water, and 0.5-4 parts by weight of 36% hydrochloric acid are uniformly mixed to obtain a precursor sol, the precursor sol is dripped onto a super-hydrophilic glass substrate to form a discontinuous liquid film, vacuum dried at 20-37° C. to reduce the water content to less than 0.5%, and a sheet is obtained, the sheet is blown off with nitrogen, the sheet is heat-treated at 500-900° C., and then appropriately crushed and sieved to obtain a mesoporous silica sheet;

[0065] Preparation of nano calcium carbonate: preparing an organic acid calcium suspension, wherein the mass concentration of the organic acid calcium is 21%-38%, adding a saturated ammonium carbonate solution, wherein the amount of ammonium carbonate added is 1.05-1.3 times the molar amount of calcium in the organic acid calcium, adding the solution uniformly, and the adding time is 20-50 minutes. The reaction temperature is 20-40° C., the stirring speed of the reaction system is 200-400 rpm, and the reaction pressure is normal pressure. After the addition of the saturated ammonium carbonate solution is completed, stirring and reacting for 40-70 minutes, filtering out the solid, washing with deionized water to neutrality, drying to a water content of less than 0.1%, and then modifying the solid with a silane coupling agent to obtain nano calcium carbonate;

[0066] Weigh the raw materials: weigh 26-33 parts by weight of polyethylene resin, 53-61 parts by weight of polypropylene resin, 1.2-2.5 parts by weight of benzoyl peroxide, 0.3-0.8 parts by weight of tert-butyl perbenzoate, 0.6-1.3 parts by weight of polyphenylene sulfide, 1.4-2.6 parts by weight of PVDF, 0.1-0.2 parts by weight of BMIMPF6 ionic liquid, 0.8-1.1 parts by weight of polymethylphenylsiloxane, 12.1-13.2 parts by weight of the mesoporous silica sheet, 0.5-0.8 parts by weight of SA500 degassing agent, 0.4-0.9 parts by weight of T961 degassing agent, 0.1-0.3 parts by weight of molybdenum oxide, 0.2-0.6 parts by weight of zinc borate, 0.06-0.2 parts by weight of ferrocene, 1.3-1.7 parts by weight of 503 leveling agent, and 5-11 parts by weight of nano calcium carbonate;

[0067] Premixing: Put the weighed raw materials into a premixing device, and premix them for 3-9 hours in an inert gas atmosphere at 280-310° C. and a stirring speed of 50-200 rpm to obtain a premix;

[0068] Melt extrusion: the premix is ​​placed in a melt extrusion device and extruded at 260-290°C and 0.3-1.4MPa to obtain plastic powder raw material particles with a particle size of 1-5 mm;

[0069] Grinding and screening: Put the plastic powder raw material particles into the grinding device, add dry ice, the mass ratio of the plastic powder raw material particles to the dry ice is maintained at 7-20:1, and the dry ice needs to be replenished intermittently in batches to keep the mass ratio of the plastic powder raw material particles to the dry ice within the range. During the grinding process, particles with a particle size of less than 100 microns are screened out, and then screened using a 50-micron aperture sieve. Particles with a particle size less than 50 microns are returned to the melt extrusion step to obtain a 50-100 micron plastic powder coating.

[0070] More preferably, the mesoporous silica sheets are pulverized using a ball mill with zirconium oxide balls, a motor speed of 2000-3000 rpm, a ball mill rotation of 1000-1300 rpm, wet ball milling, a solid-liquid ratio of 1:1.5-2.6, and a temperature of 20-38°C.

[0071] Preferably, the amine salt type cationic surfactant includes octadecylamine (stearylamine) hydrochloride, triethanolamine monostearate formate, N,N-dimethyloctadecylamine hydrochloride, and the orthosilicate includes ethyl orthosilicate and tetramethyl silicate.

[0072] Preferably, the method for preparing a super hydrophilic glass substrate comprises the following steps:

[0073] Dissolving 9-13 parts by weight of tetrabutyl titanate in 40-70 parts by weight of anhydrous ethanol, and then adding 0.03-0.08 parts by weight of glacial acetic acid to obtain a precursor solution;

[0074] Add 30-80 parts by weight of deionized water to the precursor solution for hydrolysis, react at 20-40° C. for 2-5 hours to obtain a titanium dioxide nanoparticle gel;

[0075] The titanium dioxide nanoparticle gel is sprayed onto a clean glass substrate, and dried at 25-38° C. under normal pressure to remove the solvent, thereby obtaining a glass plate pre-coated with titanium dioxide nanoparticles;

[0076] The glass plate pre-coated with titanium dioxide nanoparticles was heat treated at 350-400°C for 3-8 hours to obtain a super-hydrophilic glass substrate.

[0077] Preferably, the organic acid calcium includes calcium citrate, calcium succinate, and calcium lactate.

[0078] Preferably, the silane coupling agent includes vinyltrimethoxysilane and vinyltriethoxysilane.

[0079] It should be noted that the density of the mesoporous silica sheet of the present application is less than 1 gram / cubic centimeter, which is lower than the density of other polymer materials of plastic powder coatings. When the plastic powder coating is sprayed, it tends to float on the surface of the molten layer, so it can be enriched in the surface of the plastic powder coating after solidification. After the surface encounters fire and the surface polymer material components are burned, the mesoporous silica sheet is exposed, isolating the internal polymer material from contact with oxygen. The mesoporous silica sheet also has a high thermal insulation performance, which prevents the internal polymer component from continuing to burn at its ignition point, and plays a role in physical isolation and flame retardancy. Combined with the chemical flame retardant properties of polyphenylene sulfide and PVDF, the plastic powder coating of the present application has excellent flame retardant properties.

[0080] In order to further understand the present invention, the technical solution of the present invention is described below in conjunction with embodiments, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0081] Example 1

[0082] The plastic powder coating with flame retardant and self-cleaning properties of the present invention is prepared according to the following steps and conditions:

[0083] 9 parts by weight of tetrabutyl titanate are dissolved in 70 parts by weight of anhydrous ethanol, and then 0.03 parts by weight of glacial acetic acid are added to obtain a precursor solution; 30 parts by weight of deionized water are added to the precursor solution for hydrolysis, and the reaction is carried out at 30° C. for 3.5 hours to obtain a titanium dioxide nanoparticle gel; the titanium dioxide nanoparticle gel is sprayed onto a clean glass substrate, and dried at 25° C. under normal pressure to remove the solvent to obtain a glass plate pre-coated with titanium dioxide nanoparticles; the glass plate pre-coated with titanium dioxide nanoparticles is heat-treated at 350° C. for 3 hours to obtain a super hydrophilic glass substrate.

[0084] Preparation of mesoporous silica sheet: 3 parts by weight of octadecylamine (stearylamine) hydrochloride, 40 parts by weight of ethyl orthosilicate, 30 parts by weight of deionized water, and 0.5 parts by weight of 36% hydrochloric acid are mixed evenly to obtain a precursor sol, the precursor sol is added dropwise onto a super-hydrophilic glass substrate to form a discontinuous liquid film, and vacuum dried at 30°C to reduce the water content to less than 0.5% to obtain a sheet, the sheet is blown off with nitrogen, and the sheet is heat-treated at 500°C to obtain a mesoporous silica sheet. The grinding is carried out by a ball mill, a zirconia ball, a motor speed of 2000 rpm, a ball mill rotation of 1200 rpm, wet ball milling, a solid-liquid ratio of 1:1.5, a temperature of 28°C, and sieving to obtain mesoporous silica sheets with an average pore size of 5-9 nanometers, a pore volume of 0.8 cubic centimeters / gram, a specific surface area of ​​500 square meters / gram, a thickness of 0.5-0.9 microns, an average sheet surface diameter of 6 microns, and a density of 0.4 g / cubic centimeter;

[0085] Preparation of nano calcium carbonate: preparing a calcium citrate suspension with a mass concentration of 21%, adding a saturated ammonium carbonate solution, wherein the amount of ammonium carbonate added is 1.05 times the molar amount of calcium in the organic acid calcium, adding uniformly, and the adding time is 20 minutes. The reaction temperature is 20° C., the stirring speed of the reaction system is 200 rpm, and the reaction pressure is normal pressure. After the addition of the saturated ammonium carbonate solution is completed, stirring and reacting for 50 minutes, filtering the solid, washing it with deionized water to neutrality, drying it to a water content of less than 0.1%, and then modifying it with vinyl trimethoxysilane to obtain nano calcium carbonate with a primary crystal particle size of 20-30 nanometers;

[0086] Weigh the raw materials: weigh 26 parts by weight of polyethylene resin with a weight average molecular weight of 90000-110000, 53 parts by weight of polypropylene resin with a weight average molecular weight of 40000-60000 and an ethylene monomer content of 2.3%, 1.9 parts by weight of benzoyl peroxide, 0.3 parts by weight of tert-butyl perbenzoate, 0.6 parts by weight of polyphenylene sulfide with a weight average molecular weight of 5000-6000, 1.4 parts by weight of PVDF with a weight average molecular weight of 430,000-450,000, 0.15 parts by weight of BMIMPF6 ionic liquid, 0.8 parts by weight of polymethylphenylsiloxane, 13.2 parts by weight of mesoporous silica sheets, 0.5 parts by weight of SA500 degassing agent, 0.4 parts by weight of T961 degassing agent, 0.1 parts by weight of molybdenum oxide, 0.2 parts by weight of zinc borate, 0.1 parts by weight of ferrocene, 1.3 parts by weight of 503 leveling agent, and 5 parts by weight of nano calcium carbonate;

[0087] Premixing: The weighed raw materials are placed in a premixing device, and premixed for 6 hours at 300° C. and a stirring speed of 120 rpm in a nitrogen atmosphere to obtain a premix;

[0088] Melt extrusion: the premix is ​​placed in a melt extrusion device and extruded at 260°C and 0.3 MPa to obtain plastic powder raw material particles with a particle size of 1-2 mm;

[0089] Grinding and screening: Put the plastic powder raw material particles into the grinding device, add dry ice, the mass ratio of the plastic powder raw material particles to the dry ice is maintained at 7:1, and the dry ice needs to be replenished intermittently in batches to keep the plastic powder raw material particles and the dry ice within the above-mentioned mass ratio range. During the grinding process, particles with a particle size of less than 100 microns are screened out, and then screened using a 50-micron aperture sieve. Particles with a particle size less than 50 microns are returned to the melt extrusion step to obtain a 50-70 micron plastic powder coating.

[0090] The obtained plastic powder coating is used in a conventional spraying method, and the surface hydrophobicity and flame retardant properties of the molded plastic powder coating are tested as follows: the contact angle of water is 110°, and the result of the dynamic water drop method is 20°; the UL94 combustion test determines that its flame retardant grade reaches V0 level.

[0091] Example 2

[0092] The plastic powder coating with flame retardant and self-cleaning properties of the present invention is prepared according to the following steps and conditions:

[0093] 13 parts by weight of tetrabutyl titanate are dissolved in 55 parts by weight of anhydrous ethanol, and then 0.08 parts by weight of glacial acetic acid is added to obtain a precursor solution; 60 parts by weight of deionized water are added to the precursor solution for hydrolysis, and the reaction is carried out at 20° C. for 2 hours to obtain a titanium dioxide nanoparticle gel; the titanium dioxide nanoparticle gel is sprayed onto a clean glass substrate, and dried at 38° C. under normal pressure to remove the solvent to obtain a glass plate pre-coated with titanium dioxide nanoparticles; the glass plate pre-coated with titanium dioxide nanoparticles is heat-treated at 370° C. for 5 hours to obtain a super hydrophilic glass substrate.

[0094] Preparation of mesoporous silica sheets: 6 parts by weight of triethanolamine monostearate formate, 20 parts by weight of tetramethyl silicate, 90 parts by weight of deionized water, and 4 parts by weight of 36% hydrochloric acid are uniformly mixed to obtain a precursor sol, the precursor sol is dropped onto a super-hydrophilic glass substrate to form a discontinuous liquid film, and vacuum dried at 20°C to reduce the water content to less than 0.5% to obtain a sheet, the sheet is blown off with nitrogen, the sheet is heat-treated at 700°C, and the mesoporous silica sheet is crushed. A ball mill was used, a zirconia ball was used, a motor speed of 3000 rpm, a ball mill jar was rotated at 1000 rpm, wet ball milling was performed, a solid-liquid ratio of 1:2.6, a temperature of 20°C, and sieving was performed to obtain mesoporous silica sheets with an average pore diameter of 10-15 nanometers, a pore volume of 0.7 cubic centimeters per gram, a specific surface area of ​​550 square meters per gram, a thickness of 0.8-1.1 micrometers, an average sheet surface diameter of 10 micrometers, and a density of 0.66 g / cubic centimeter;

[0095] Preparation of nano calcium carbonate: preparing a calcium succinate suspension with a mass concentration of 38%, adding a saturated ammonium carbonate solution, wherein the amount of ammonium carbonate added is 1.2 times the molar amount of calcium in the organic acid calcium, adding uniformly, and the adding time is 35 minutes. The reaction temperature is 40° C., the stirring speed of the reaction system is 300 rpm, and the reaction pressure is normal pressure. After the addition of the saturated ammonium carbonate solution is completed, stirring and reacting for 40 minutes, filtering the solid, washing it with deionized water to neutrality, drying it to a water content of less than 0.1%, and then modifying it with vinyl triethoxysilane to obtain nano calcium carbonate with a primary crystal particle size of 30-50 nanometers;

[0096] Weigh the raw materials: weigh 33 parts by weight of polyethylene resin with a weight average molecular weight of 150000-200000, 61 parts by weight of polypropylene resin with a weight average molecular weight of 25000-30000 and an ethylene monomer content of 3.0%, 1.2 parts by weight of benzoyl peroxide, 0.8 parts by weight of tert-butyl perbenzoate, 1.0 parts by weight of polyphenylene sulfide with a weight average molecular weight of 6000-7000, 2.6 parts by weight of PVDF with a weight average molecular weight of 410,000-430,000, 0.1 parts by weight of BMIMPF6 ionic liquid, 1.1 parts by weight of polymethylphenylsiloxane, 12.1 parts by weight of mesoporous silica sheets, 0.7 parts by weight of SA500 degassing agent, 0.9 parts by weight of T961 degassing agent, 0.2 parts by weight of molybdenum oxide, 0.6 parts by weight of zinc borate, 0.06 parts by weight of ferrocene, 1.7 parts by weight of 503 leveling agent, and 8 parts by weight of nano calcium carbonate;

[0097] Premixing: The weighed raw materials are placed in a premixing device, and premixed for 9 hours at 280° C. and a stirring speed of 200 rpm in a nitrogen atmosphere to obtain a premix;

[0098] Melt extrusion: the premix is ​​placed in a melt extruder and extruded at 275°C and 1.4 MPa to obtain plastic powder raw material particles with a particle size of 2-4 mm;

[0099] Grinding and screening: Put the plastic powder raw material particles into the grinding device, add dry ice, the mass ratio of the plastic powder raw material particles to the dry ice is maintained at 14:1, and the dry ice needs to be replenished intermittently in batches to keep the plastic powder raw material particles and the dry ice within the above-mentioned mass ratio range. During the grinding process, particles with a particle size of less than 100 microns are screened out, and then screened using a 50-micron aperture sieve. Particles with a particle size less than 50 microns are returned to the melt extrusion step to obtain a 70-100 micron plastic powder coating.

[0100] The obtained plastic powder coating is used in a conventional spraying method, and the surface hydrophobicity and flame retardant properties of the molded plastic powder coating are tested as follows: the contact angle of water is 97°, and the result of the dynamic water drop method is 27°; the UL94 combustion test determines that its flame retardant grade reaches V0 level.

[0101] Example 3

[0102] The plastic powder coating with flame retardant and self-cleaning properties of the present invention is prepared according to the following steps and conditions:

[0103] 11 parts by weight of tetrabutyl titanate are dissolved in 40 parts by weight of anhydrous ethanol, and then 0.005 parts by weight of glacial acetic acid is added to obtain a precursor solution; 80 parts by weight of deionized water are added to the precursor solution for hydrolysis, and the reaction is carried out at 40° C. for 5 hours to obtain a titanium dioxide nanoparticle gel; the titanium dioxide nanoparticle gel is sprayed onto a clean glass substrate, and dried at 30° C. under normal pressure to remove the solvent to obtain a glass plate pre-coated with titanium dioxide nanoparticles; the glass plate pre-coated with titanium dioxide nanoparticles is heat-treated at 400° C. for 8 hours to obtain a super hydrophilic glass substrate.

[0104] Preparation of mesoporous silica wafers: 4.5 parts by weight of N,N-dimethyloctadecylamine hydrochloride, 50 parts by weight of ethyl orthosilicate, 60 parts by weight of deionized water, and 2 parts by weight of 36% hydrochloric acid were uniformly mixed to obtain a precursor sol, the precursor sol was dropped onto a super-hydrophilic glass substrate to form a discontinuous liquid film, and vacuum dried at 37°C to reduce the water content to less than 0.5% to obtain a sheet layer, the sheet layer was blown off with nitrogen, and the sheet layer was heat-treated at 900°C to obtain a mesoporous silica wafer. The grinding is carried out by a ball mill, a zirconia ball, a motor speed of 2500 rpm, a ball mill rotation of 1300 rpm, wet ball milling, a solid-liquid ratio of 1:2, a temperature of 38°C, and sieving to obtain mesoporous silica sheets with an average pore size of 8-13 nanometers, a pore volume of 0.9 cubic centimeters / gram, a specific surface area of ​​600 square meters / gram, a thickness of 0.7-1.0 microns, an average sheet surface diameter of 13 microns, and a density of 0.25 g / cubic centimeter;

[0105] Preparation of nano calcium carbonate: preparing a calcium lactate suspension with a mass concentration of 30%, adding a saturated ammonium carbonate solution, wherein the amount of ammonium carbonate added is 1.3 times the molar amount of calcium in the organic acid calcium, adding uniformly, and the adding time is 50 minutes. The reaction temperature is 30° C., the stirring speed of the reaction system is 400 rpm, and the reaction pressure is normal pressure. After the addition of the saturated ammonium carbonate solution is completed, stirring and reacting for 70 minutes, filtering the solid, washing it with deionized water to neutrality, drying it to a water content of less than 0.1%, and then modifying it with vinyl trimethoxysilane to obtain nano calcium carbonate with a primary crystal particle size of 40-70 nanometers;

[0106] Weigh the raw materials: weigh 30 parts by weight of polyethylene resin with a weight average molecular weight of 100000-160000, 58 parts by weight of polypropylene resin with a weight average molecular weight of 30000-45000 and an ethylene monomer content of 4.2%, 2.5 parts by weight of benzoyl peroxide, 0.5 parts by weight of tert-butyl perbenzoate, 1.3 parts by weight of polyphenylene sulfide with a weight average molecular weight of 5500-6500, 1.9 parts by weight of PVDF with a weight average molecular weight of 400,000-420,000, 0.2 parts by weight of BMIMPF6 ionic liquid, 0.95 parts by weight of polymethylphenylsiloxane, 12.8 parts by weight of mesoporous silica sheets, 0.8 parts by weight of SA500 degassing agent, 0.7 parts by weight of T961 degassing agent, 0.3 parts by weight of molybdenum oxide, 0.4 parts by weight of zinc borate, 0.2 parts by weight of ferrocene, 1.5 parts by weight of 503 leveling agent, and 11 parts by weight of nano calcium carbonate;

[0107] Premixing: The weighed raw materials were placed in a premixing device, and premixed for 3 hours at 310° C. and a stirring speed of 50 rpm in a nitrogen atmosphere to obtain a premix;

[0108] Melt extrusion: the premix is ​​placed in a melt extrusion device and extruded at 290°C and 0.8 MPa to obtain plastic powder raw material particles with a particle size of 3-5 mm;

[0109] Grinding and screening: Put the plastic powder raw material particles into the grinding device, add dry ice, the mass of the plastic powder raw material particles and dry ice is maintained at 20:1, and the dry ice needs to be replenished intermittently in batches to keep the plastic powder raw material particles and dry ice within the above-mentioned mass ratio range. During the grinding process, particles with a particle size of less than 100 microns are screened out, and then screened using a 50-micron aperture sieve. Particles with a particle size less than 50 microns are returned to the melt extrusion step to obtain a 60-80 micron plastic powder coating.

[0110] The obtained plastic powder coating is used in a conventional spraying method, and the surface hydrophobicity and flame retardant properties of the molded plastic powder coating are tested as follows: the contact angle of water is 120°, and the result of the dynamic water drop method is 15°; the UL94 combustion test determines that its flame retardant grade reaches V0 level.

[0111] Comparative Example 1

[0112] No mesoporous silica flakes are added to the plastic powder coating component of this comparative example, and there are no steps for preparing the mesoporous silica flakes and the super-hydrophilic glass substrate. The rest is the same as Example 3.

[0113] The obtained plastic powder coating is used in a conventional spraying method, and the flame retardant properties of the molded plastic powder coating are tested as follows: the flame retardant grade thereof is V1 grade as determined by the UL94 combustion test.

[0114] Comparative Example 2

[0115] The plastic powder coating components of this comparative example do not contain polyphenylene sulfide and PVDF flame retardant, and the rest are the same as those in Example 3.

[0116] The obtained plastic powder coating is used in a conventional spraying method, and the flame retardant properties of the molded plastic powder coating are tested as follows: the flame retardant grade thereof is V2 grade as determined by the UL94 combustion test.

[0117] Comparative Example 3

[0118] The plastic powder coating component of this comparative example does not contain polymethylphenylsiloxane, and the rest is the same as that of Example 3.

[0119] The obtained plastic powder coating was used in a conventional spraying method, and the surface hydrophobicity of the molded plastic powder coating was tested as follows: the contact angle of water was 77°, and the result of the dynamic water drop method was 34°.

[0120] Comparative Example 4

[0121] The plastic powder coating component of this comparative example does not contain BMIMPF6 ionic liquid, and the rest is the same as Example 3.

[0122] The obtained plastic powder coating was used in a conventional spraying method. The surface hydrophobicity of the molded plastic powder coating was tested as follows: the contact angle of water was 81°, and the result of the dynamic water drop method was 32°.

[0123] Through the comparison of the above embodiments and comparative examples, it can be seen that the introduction of mesoporous silica sheets can significantly improve the flame retardant properties of the plastic powder coating of the present application, and can further improve its flame retardant ability when used in combination with other chemical flame retardants; at the same time, after the introduction of BMIMPF6 ionic liquid and polymethylphenylsiloxane, its surface hydrophobicity is increased, and the two have a synergistic effect.

Claims

1. A plastic powder coating with flame retardant and self-cleaning properties, characterized in that: The plastic powder coating comprises a base resin, a cross-linking agent, a self-cleaning agent, a flame retardant, a degassing agent, a smoke suppressant, a leveling agent, and a filler; The base resin includes 26-33 parts by weight of polyethylene resin and 53-61 parts by weight of polypropylene resin; The cross-linking agent comprises 1.2-2.5 parts by weight of benzoyl peroxide and 0.3-0.8 parts by weight of tert-butyl perbenzoate; The self-cleaning agent comprises 0.6-1.3 parts by weight of polyphenylene sulfide, 1.4-2.6 parts by weight of PVDF, 0.1-0.2 parts by weight of BMIMPF6 ionic liquid, and 0.8-1.1 parts by weight of polymethylphenylsiloxane; The flame retardant comprises 12.1-13.2 parts by weight of mesoporous silica sheets; The degassing agent includes 0.5-0.8 parts by weight of SA500 degassing agent and 0.4-0.9 parts by weight of KT961 degassing agent; The smoke suppressant comprises 0.1-0.3 parts by weight of molybdenum oxide, 0.2-0.6 parts by weight of zinc borate, and 0.06-0.2 parts by weight of ferrocene; The leveling agent includes 1.3-1.7 parts by weight of 503 leveling agent; The filler comprises 5-11 parts by weight of nano calcium carbonate; The particle size of the plastic powder coating is 50-100 microns; The preparation method of the mesoporous silica sheet is as follows: 3-6 parts by weight of an amine salt type cationic surfactant, 20-50 parts by weight of an orthosilicate, 30-90 parts by weight of deionized water, and 0.5-4 parts by weight of 36% hydrochloric acid are uniformly mixed to obtain a precursor sol, the precursor sol is dripped onto a super-hydrophilic glass substrate to form a discontinuous liquid film, vacuum dried at 20-37° C. to make the water content less than 0.5%, to obtain a sheet layer, the sheet layer is blown off with nitrogen, the sheet layer is heat-treated at 500-900° C., and then appropriately crushed and sieved to obtain the mesoporous silica sheet; The preparation method of the nano calcium carbonate is as follows: preparing an organic acid calcium suspension with a mass concentration of 21%-38%, adding a saturated ammonium carbonate solution, wherein the amount of ammonium carbonate added is 1.05-1.3 times the molar amount of calcium in the organic acid calcium, adding the solution evenly, and the adding time is 20-50 minutes. The reaction temperature is 20-40° C., the stirring speed of the reaction system is 200-400 rpm, and the reaction pressure is normal pressure. After the addition of the saturated ammonium carbonate solution is completed, stirring and reacting for 40-70 minutes, filtering the solid, washing it with deionized water until it is neutral, drying it to a water content of less than 0.1%, and then modifying it with a silane coupling agent to obtain the nano calcium carbonate.

2. The flame retardant and self-cleaning plastic powder coating according to claim 1, characterized in that: The mesoporous silica sheet has an average pore diameter of 5-15 nanometers, a pore volume of 0.7-0.9 cubic centimeters / gram, a specific surface area of ​​500-600 square meters / gram, a thickness of 0.5-1.1 micrometers, and an average sheet surface diameter of 6-13 micrometers.

3. The flame retardant and self-cleaning plastic powder coating according to claim 1, characterized in that: The primary crystal grain size of the nano calcium carbonate is 20-70 nanometers, and the secondary crystal grain size is 1-2 micrometers.

4. The flame retardant and self-cleaning plastic powder coating according to claim 1, characterized in that: The polyethylene resin is high-density polyethylene with a weight average molecular weight of 90,000-200,000.

5. The flame retardant and self-cleaning plastic powder coating according to claim 1, characterized in that: The polypropylene resin is random copolymer polypropylene with a weight average molecular weight of 25,000-60,000 and an ethylene monomer content of 2.3%-4.2%.

6. A method for preparing a plastic powder coating having flame retardant and self-cleaning properties as claimed in any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: Preparation of mesoporous silica sheets: 3-6 parts by weight of an amine salt type cationic surfactant, 20-50 parts by weight of an orthosilicate, 30-90 parts by weight of deionized water, and 0.5-4 parts by weight of 36% hydrochloric acid are uniformly mixed to obtain a precursor sol, the precursor sol is dripped onto a super-hydrophilic glass substrate to form a discontinuous liquid film, vacuum dried at 20-37° C. to reduce the water content to less than 0.5%, to obtain a sheet, the sheet is blown off with nitrogen, the sheet is heat-treated at 500-900° C., and then appropriately crushed and sieved to obtain the mesoporous silica sheet; Preparation of nano calcium carbonate: preparing an organic acid calcium suspension, wherein the mass concentration of organic acid calcium is 21%-38%, adding a saturated ammonium carbonate solution, wherein the amount of ammonium carbonate added is 1.05-1.3 times the molar amount of calcium in the organic acid calcium, adding uniformly, and the adding time is 20-50 minutes. The reaction temperature is 20-40° C., the stirring speed of the reaction system is 200-400 rpm, and the reaction pressure is normal pressure. After the addition of the saturated ammonium carbonate solution is completed, stirring and reacting for 40-70 minutes, filtering the solid, washing with deionized water to neutrality, drying to a water content of less than 0.1%, and then modifying with a silane coupling agent to obtain the nano calcium carbonate; Weigh the raw materials: weigh 26-33 parts by weight of polyethylene resin, 53-61 parts by weight of polypropylene resin, 1.2-2.5 parts by weight of benzoyl peroxide, 0.3-0.8 parts by weight of tert-butyl perbenzoate, 0.6-1.3 parts by weight of polyphenylene sulfide, 1.4-2.6 parts by weight of PVDF, 0.1-0.2 parts by weight of BMIMPF6 ionic liquid, 0.8-1.1 parts by weight of polymethylphenylsiloxane, 12.1-13.2 parts by weight of the mesoporous silica sheet, 0.5-0.8 parts by weight of SA500 degassing agent, 0.4-0.9 parts by weight of T961 degassing agent, 0.1-0.3 parts by weight of molybdenum oxide, 0.2-0.6 parts by weight of zinc borate, 0.06-0.2 parts by weight of ferrocene, 1.3-1.7 parts by weight of 503 leveling agent, and 5-11 parts by weight of nano calcium carbonate; Premixing: Put the weighed raw materials into a premixing device, and premix them for 3-9 hours in an inert gas atmosphere at 280-310° C. and a stirring speed of 50-200 rpm to obtain a premix; Melt extrusion: the premix is ​​placed in a melt extrusion device and extruded at 260-290°C and 0.3-1.4MPa to obtain plastic powder raw material particles with a particle size of 1-5 mm; Grinding and screening: the plastic powder raw material particles are placed in a grinding device, and dry ice is added. The mass ratio of the plastic powder raw material particles to the dry ice is maintained at 7-20:

1. The dry ice needs to be replenished intermittently in batches to keep the mass ratio of the plastic powder raw material particles to the dry ice within the range. During the grinding process, particles with a particle size of less than 100 microns are screened out, and then screened using a 50-micron aperture sieve. Particles with a particle size less than 50 microns are returned to the melt extrusion step to obtain a 50-100 micron plastic powder coating.

7. The method for preparing the plastic powder coating with flame retardant and self-cleaning properties according to claim 6, characterized in that: The amine salt type cationic surfactant includes octadecylamine hydrochloride, triethanolamine monostearate formate, and N,N-dimethyloctadecylamine hydrochloride, and the orthosilicate includes ethyl orthosilicate and tetramethyl silicate.

8. The method for preparing the plastic powder coating with flame retardant and self-cleaning properties according to claim 6, characterized in that: The method for preparing a super hydrophilic glass substrate comprises the following steps: Dissolving 9-13 parts by weight of tetrabutyl titanate in 40-70 parts by weight of anhydrous ethanol, and then adding 0.03-0.08 parts by weight of glacial acetic acid to obtain a precursor solution; Add 30-80 parts by weight of deionized water to the precursor solution for hydrolysis, react at 20-40° C. for 2-5 hours to obtain a titanium dioxide nanoparticle gel; The titanium dioxide nanoparticle gel is sprayed onto a clean glass substrate, and dried at 25-38° C. under normal pressure to remove the solvent, thereby obtaining a glass plate pre-coated with titanium dioxide nanoparticles; The glass plate pre-coated with titanium dioxide nanoparticles is heat-treated at 350-400° C. for 3-8 hours to obtain the super-hydrophilic glass substrate.

9. The method for preparing the plastic powder coating with flame retardant and self-cleaning properties according to claim 6, characterized in that: The organic acid calcium includes calcium citrate, calcium succinate and calcium lactate.

10. The method for preparing the plastic powder coating with flame retardant and self-cleaning properties according to claim 6, characterized in that: The silane coupling agent includes vinyl trimethoxy silane and vinyl triethoxy silane.